Emerging therapeutic targets for cerebral edema. (2nd November 2021) - Jha, Ruchira M.; Raikwar, Sudhanshu P.; Mihaljevic, Sandra; Casabella, Amanda M.; Catapano, Joshua S.; Rani, Anupama; Desai, Shashvat; Gerzanich, Volodymyr; Simard, J. Marc
ABSTRACT: Introduction: Cerebral edema is a key contributor to death and disability in several forms of brain injury. Current treatment options are limited, reactive, and associated with significant morbidity. Targeted therapies are emerging based on a growing understanding of the molecular underpinnings of cerebral edema. Areas Covered: We review the pathophysiology and relationships between different cerebral edema subtypes to provide a foundation for emerging therapies. Mechanisms for promising molecular targets are discussed, with an emphasis on those advancing in clinical trials, including ion and water channels (AQP4, SUR1-TRPM4) and other proteins/lipids involved in edema signaling pathways (AVP, COX2, VEGF, and S1P). Research on novel treatment modalities for cerebral edema [including recombinant proteins and gene therapies] is presented and finally, insights on reducing secondary injury and improving clinical outcome are offered. Expert Opinion: Targeted molecular strategies to minimize or prevent cerebral edema are promising. Inhibition of SUR1-TRPM4 (glyburide/glibenclamide) and VEGF (bevacizumab) are currently closest to translation based on advances in clinical trials. However, the latter, tested in glioblastoma multiforme, has not demonstrated survival benefit. Research on recombinant proteins and gene therapies for cerebral edema is in its infancy, but early results are encouraging. These newer modalities may facilitate our understanding of the pathobiology underlying cerebral edema.